Analisis Strategi Pengembangan Pariwisata Bahari Kota Ternate Provinsi Maluku Utara - Betly Taghulihi; Vidhia Hirto (SENTRI: Jurnal Riset Ilmiah, 2025)
North Maluku has considerable potential for the development of tourism based on fisheries and marine resources, particularly in Ternate City, which is well known for its marine natural beauty and rich local wisdom. Marine tourism represents a strategic sector that needs to be managed in a well-directed and sustainable manner. Although the identification of internal and external factors indicates significant development opportunities, marine tourism in Ternate City continues to face various challenges, including limited supporting infrastructure, suboptimal tourism service quality, weak institutional capacity, and increasing pressure on coastal environments. These conditions highlight the urgency of formulating marine tourism development strategies that are capable of optimizing existing potential while minimizing current weaknesses and challenges. This study aims to formulate development strategies for marine tourism in Ternate City by employing a qualitative descriptive–exploratory approach supported by SWOT analysis. Data were collected through field observations, in-depth interviews with key stakeholders, and reviews of relevant planning and policy documents. The results of the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrix analyses indicate that the strategic position of marine tourism in Ternate City falls within the WO quadrant (Quadrant III), suggesting dominant internal weaknesses despite relatively strong external opportunities. The main contribution of this study lies in the formulation of corrective strategies based on local social, environmental, and institutional conditions within a small-island context. Practically, the findings provide important implications for local governments, tourism authorities, tourism awareness groups, and business stakeholders in formulating destination development policies, strengthening coastal community capacity, and promoting sustainable marine tourism management oriented toward improving local community welfare.